2013
DOI: 10.33073/pjm-2013-033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Molecular Diversity in Chickpea (Cicer arietinum L.) Rhizobia and Structural Analysis of 16S rDNA Sequences from Mesorhizobium ciceri

Abstract: Molecular diversity studies of 19 rhizobia isolates from chickpea were conducted using simple sequence repeats (SSR) and 16S rDNA-RFLP markers. Phenotypic characterization with special reference to salinity and pH tolerance was performed. These isolates were identified as different strains of Mesorhizobium, Rhizobium, Bradyrhizobium, and Agrobacterium. Twenty SSR loci of Mesorhizobium ciceri, distributed across the other rhizobial genome, clearly differentiated 19 rhizobial isolates. Analogous clustering suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The rhizobialegume symbiosis enhances the N 2 fixation and productivity of legume yields which correlate to the quality of inoculant strain and physiological state of the host plant (Verma et al 2010;Jida and Assefa 2012;Laranjo et al 2014). Several studies indicate that rhizobium inoculants may not be able to express their full capacity of nitrogen fixation under stress conditions (Rai et al 2012;Yadav et al 2013) because the environmental factors such as soil acidity, salinity, nutrient deficiency and extreme temperature have negative effect on the legume nodulation and even limiting the vigor of the legume host (Laranjo et al 2014). Hence, rhizobium strains which are used for agricultural applications as inoculants must be competitive for nodule occupancy and nitrogen fixation even under extreme physiological stress.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizobialegume symbiosis enhances the N 2 fixation and productivity of legume yields which correlate to the quality of inoculant strain and physiological state of the host plant (Verma et al 2010;Jida and Assefa 2012;Laranjo et al 2014). Several studies indicate that rhizobium inoculants may not be able to express their full capacity of nitrogen fixation under stress conditions (Rai et al 2012;Yadav et al 2013) because the environmental factors such as soil acidity, salinity, nutrient deficiency and extreme temperature have negative effect on the legume nodulation and even limiting the vigor of the legume host (Laranjo et al 2014). Hence, rhizobium strains which are used for agricultural applications as inoculants must be competitive for nodule occupancy and nitrogen fixation even under extreme physiological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we observed that R30 and R31 have a phylogenetic relationship with a chickpeanodulating strain named Ca181 and classified as an M. ciceri (Yadav et al, 2013), whose phylogenetic position has not been confirmed. From reports that compare rhizobia isolated from chickpea nodules with different Mesorhizobium strains, Ca181 could be inferred to be in a separate cluster from other M. ciceri strains (Singh et al, 2019;Yadav et al, 2013), in agreement with our study. In sum, this strain is likely a different species from M. ciceri, but more research is necessary.…”
Section: Resultsmentioning
confidence: 85%
“…Shinella and Mesorhizobium are known to establish a symbiosis with legumes (Muleta et al, 2022; Wang, 2019). Particularly, Mesorhizobium has been reported to specifically nodulate with chickpea plants (Muleta et al, 2022; Yadav et al, 2013, 2021). When rhizobia form effective nodules in the plant roots, the bacteria fix atmospheric nitrogen in the form of ‘ready‐to‐use’ ammonia.…”
Section: Discussionmentioning
confidence: 99%